Talking about cross-talk: the immune system and the microbiome. Issue 1 (December 2016) - Zeevi, David; Korem, Tal; Segal, Eran
Abstract A report on the first EMBO conference entitled "Next Gen Immunology—From Host Genome to the Microbiome: Immunity in the Genomic Era", held at the Weizmann Institute of Science, Israel, 14–16 February, 2016.